HUBUNGAN ANTARA ASPEK KESEHATAN MENTAL DAN PERSEPSI TENTANG PEMBELAJARAN DARING TERHADAP INDEKS PRESTASI KUMULATIF MAHASISWA MAUPUN MAHASISWI DI FAKULTAS KEDOKTERAN HKBP NOMMENSEN - JOICE SONYA GANI PANJAITAN; SUHARTOMI . (JURNAL ILMIAH SIMANTEK, 2022)
The pandemic has greatly impacted students, resulting in the lecture system that was originally face-to-face to online,moreover the harder task with anxiety about online study achievement. To evaluate the relationship between mental healthaspects and perceptions of online learning system on the grade point average (GPA) among students at the Faculty ofMedicine, Universitas HKBP Nommensen. This study is a cross-sectional study on 88 students at the Faculty of Medicine,Universitas HKBP Nommensen between October-November 2021, selected by the accidental sampling method. Aspects ofmental health (Depression, Anxiety, and Stress) and perceptions about online learning were evaluated by an onlinequestionnaire. Meanwhile, the statistical analysis used to achieve the research objectives was chi-square as bivariateanalysis and logistic regression as multivariate analysis. There was no significant relationship between anxiety, stress, andperceptions of online learning on the GPA of students at the Faculty of Medicine, Universitas HKBP Nommensen (P value >0.05). Interestingly, only depression significantly affected the GPA scores of students at the Faculty of Medicine, UniversitasHKBP Nommensen (P value < 0.05; OR [95% CI]: 4,207 [1,340-13,212]). Only depression significantly affects the GPA ofmedical students during the COVID-19 pandemic.